Quality of Life of Mothers of Children with Cerebral Palsy and their Age-matched Controls (2014)
Background: Caring for a child with cerebral palsy (CP) could negatively impact the quality of life (QoL) of the mothers who are usually the primary caregivers. Studies on the impact of caring for Nigerian children with cerebral palsy on the mothers’ quality of life are not common hence the quality of life of mothers of children with cerebral palsy (MCCP) and age-matched mothers of typically developing children (MTDC) were compared in this study. Methods: Eighty mothers (40 MCCP and 40 MTDC) participated in this cross-sectional survey. Participants in both groups had their quality of life assessed using the World Health Organization Quality of Life BREF (WHOQoL-BREF). Data were analyzed using independent t-test, Chi-square and Mann-Whitney U tests with alpha level set at 0.05. Results: The two groups were not significantly different in their ages (p = 0.14). The mean overall QoL score of the MCCP (62.83±17.83) was significantly lower than that of the MTDC (68.87±8.51) (U=590.0; p=0.04) just as scores for overall health perception (U=576.5; p=0.03). Religion, educational status and occupational status had no significant influence on the QoL scores of mothers of children with cerebral palsy. Conclusion: Caring for a child with CP significantly impacted on the QOL and health of the mothers, irrespective of their socio-economic status. Measures to improve quality of life and health of mothers of children with cerebral palsy should be incorporated in the management of CP with emphasis on identified areas of need.